Impact Of Gender on Job Satisfaction And Organizational Commitment In Manufacturing Sector - Singh, Dhara; Kumar, Sanjeev; Meet, Manoj Kumar (International Journal of Membrane Science and Technology, 2023)
These days, in the field of research, specially, job satisfaction has developed as one of the most preferred and doable topics. The business institutions are more concern over the effect on the performance of the organizations. Job satisfaction is connected to the effective response to the working environment and organizational commitment is considered as more consistent and continuing attitudes of employees. Many studies have found that job satisfaction and organizational commitment play vital role in the growth and development of an organization. Any organization is not be able to attain the competitive level of excellence, from the product point of view or from the customer point of view, without taking into consideration the satisfaction level of its employees. In this study, effect of gender on both the attitudes of a person – job satisfaction and organizational commitment has been investigated. The responses of employees from manufacturing sectors have been collected and analysed to get the result. It revealed that men and women have similar level of job satisfaction and organizational commitment.